Sustainability Assessment of Biorefinery Systems Based on Two Food Residues in Africa - Patrizi, Nicoletta; Bruno, Morena; Saladini, Fabrizio; Parisi, Maria Laura; Pulselli, Riccardo M.; Bjerre, Anne Belinda; Bastianoni, Simone (Frontiers in Sustainable Food Systems, 2020)
The overexploitation of fossil fuels as main energy source to support the global economy is identified as the most responsible of the current critical situation from an environmental viewpoint. The need to replace fossil fuels has posed the attention on alternative energy sources such as biofuels, in both developed and developing countries. Africa, for example, has enormous natural resources in the form of biomass from agriculture and other related processes (i.e. food residues). An action that can help fight climate change is the implementation of biofuel refineries to maximize the value of biomass by converting it into a range of products, like energy vectors, biomaterials, feed and fertilizers. By using emergy evaluation and Life Cycle Assessment (LCA) this study focused on the potential development of sustainable biotechnological processes fed by biowaste and bioresidues in two African countries (Egypt and Ghana). We assessed the sustainability level of two biofuel productions based on starch and lignocellulosic feedstocks (i.e. cassava peel and corn stover, respectively). A first understanding of the sustainability of the case studies was obtained and the results showed that the biorefinery based on cassava peel was more sustainable from both the user and donor perspectives. Indeed, the LCA results showed that impact categories Global Warming Potential (GWP) and Acidification Potential (AP) had lower values for cassava compared to corn stover biorefinery and emergy outcomes highlighted that the starch-rich feedstock had lower Unit Emergy Value (UEV) and higher renewability percentage (94%). These results suggest that biorefineries are an option for world bioeconomy strategy as they enable optimization of agricultural and food residues and their environmental performance in producing a renewable substitute for fossil fuels and other non-renewable materials is promising.